Effect of a High-Fat Diet and Occupational Exposure in Different Rat Strains on Lung and Systemic Responses: Examination of the Exposome in an Animal Model. (26th December 2019) - Antonini, James M; Kodali, Vamsi; Shoeb, Mohammad; Kashon, Michael; Roach, Katherine A; Boyce, Gregory; Meighan, Terence; Stone, Samuel; McKinney, Walter; Boots, Theresa; Roberts, Jenny R; Zeidler-Erdely, Patti C; et al.
Abstract: The exposome is the measure of all exposures of an individual in a lifetime and how those exposures relate to health. The goal was to examine an experimental model integrating multiple aspects of the exposome by collecting biological samples during critical life stages of an exposed animal that are applicable to worker populations. Genetic contributions were assessed using strains of male rats with different genetic backgrounds (Fischer-344, Sprague Dawley, and Brown-Norway) maintained on a regular or high-fat diet for 24 weeks. At week 7 during diet maintenance, groups of rats from each strain were exposed to stainless steel welding fume (WF; 20 mg/m 3 × 3 h/d × 4 days/week × 5 weeks) or air until week 12, at which time some animals were euthanized. A separate set of rats from each strain were allowed to recover from WF exposure until the end of the 24-week period. Bronchoalveolar lavage fluid and serum were collected at 7, 12, and 24 weeks to assess general health indices. Depending on animal strain, WF exposure and high-fat diet together worsened kidney toxicity as well as altered different serum enzymes and proteins. Diet had minimal interaction with WF exposure for pulmonary toxicity endpoints. Experimental factors of diet, exposure, and strain were all important, depending on the health outcome measured. Exposure had the most significant influence related to pulmonary responses. Strain was the most significant contributor regarding the other health indices examined, indicating that genetic differences possibly drive the exposome effect in each strain.